Communications Apprehension: A Note About Ethnic Diversity - Aly, Ibrahim M.; Gowing, Maureen P. Sterling (Canadian Journal of Higher Education, 2001)
This paper summarizes the results of an intercultural survey of an ethnically diverse group of students in a Canadian university commerce program. The sample self-reported the level of communications apprehension on the 24-item Personal Report of Communication Apprehension, which uses six questions in four communications settings to generate four subscores and one general score for communications apprehension (McCroskey, 1982). While prior research results showed that the level of communications apprehension varies among ethnic groups, our research results showed no significant variation.